Proceedings of International Conference on Power Electronics, Drives and Energy Systems for Industrial Growth
DOI: 10.1109/pedes.1996.539678
|View full text |Cite
|
Sign up to set email alerts
|

Current harmonics generated by electric vehicle battery chargers

Abstract: This paper presents the results and analysis of data collected in the three groups of electrio vehicle battery chargers during three coiisecutive years: 1993, 1994, and 1995. The first group of battery chargers consisted of 27 chargers. The generated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Based on literature, it can be concluded that over time and with the development of power supply technologies, the amount of distortion from EV charging has decreased. Measurements in the 1990's showed that the use of uncontrolled or low-control rectifiers caused average current THD of 50% [19]. Measurements of modern commercial EVs have indicated an average charging current THD around 11%…12% [20] [21], but values as low as 4.5% [22] have also been indicated.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on literature, it can be concluded that over time and with the development of power supply technologies, the amount of distortion from EV charging has decreased. Measurements in the 1990's showed that the use of uncontrolled or low-control rectifiers caused average current THD of 50% [19]. Measurements of modern commercial EVs have indicated an average charging current THD around 11%…12% [20] [21], but values as low as 4.5% [22] have also been indicated.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on the literature it can be concluded that over the years the amount of distortion from EV charging has decreased. The measurement in the 90's showed that the use of uncontrolled or low-control rectifiers causes average THD_i of 50% [7].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of energy and power density, ultra capacitors can therefore be placed between batteries and conventional capacitors [4][5]. An ultra-capacitor is an electrochemical component which mimics characteristics of very high value capacitors.…”
Section: Introductionmentioning
confidence: 99%